Demensi Sosial dan Spiritual Semaan Al-Qur'an "MANTAB" di Yogyakarta - Suyatno Prodjodikoro (Al-Jami'ah: Journal of Islamic Studies, 2001)
The development of al-Qur'an recitation gathering named “Mantab” in Yogyakarta is a socio-religious phenomenon. This effort of spiritualization of Islamic teachings attracts many participants. Mass pray and recitation of all content of the Holy Book, al-Qur'an, are main rituals held in this gathering. The participants use al-Qur'an recitation (semaan) gathering as a mean of spiritual exercises that can guide them to acquire deep inner happiness.Besides spiritual nuance, al-Qur'an recitation of “Mantab” has also social effects. It can strengthen the relationship among the participants whether they come from higher or lower strata of society, such as religious leaders and grassroots. In this gathering, they can communicate each other. Therefore, the al-Qur'an recitation has social function as well. Religious leaders who have deep esoteric nuance and are supported by their good social legitimacy, have central position in social structure of this gathering. Consequently, "asking blessing" and "Patron-Client,' can easily be seen in social interaction in this gathering.